2018
DOI: 10.1155/2018/5798103
|View full text |Cite
|
Sign up to set email alerts
|

Audiovestibular Symptoms in Systemic Autoimmune Diseases

Abstract: Immune-mediated inner ear disease can be primary, when the autoimmune response is against the inner ear, or secondary. The latter is characterized by the involvement of the ear in the presence of systemic autoimmune conditions. Sensorineural hearing loss is the most common audiovestibular symptom associated with systemic autoimmune diseases, although conductive hearing impairment may also be present. Hearing loss may present in a sudden, slowly, rapidly progressive or fluctuating form, and is mostly bilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 135 publications
3
68
0
Order By: Relevance
“…33,34 Autoimmune MD Animal studies demonstrated the induction of antibodies production by the inner ear, giving further evidence that the endolymphatic sac has an immune function. 35,36 Human studies have demonstrated the presence of autoantigens against the inner ear, both in MD and in autoimmune inner ear disease. Regarding MD, several hypotheses have been proposed to explain the appearance of autoimmune responses in the inner ear, including the appearance of cross-reactions with shared epitopes between inner ear proteins and microbial proteins, the induction of damage associated with sustained high levels of cytokines and chemokines, or the presence of immunogenic factors producing a persistent inflammatory response in the inner ear.…”
Section: Genetic MDmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 Autoimmune MD Animal studies demonstrated the induction of antibodies production by the inner ear, giving further evidence that the endolymphatic sac has an immune function. 35,36 Human studies have demonstrated the presence of autoantigens against the inner ear, both in MD and in autoimmune inner ear disease. Regarding MD, several hypotheses have been proposed to explain the appearance of autoimmune responses in the inner ear, including the appearance of cross-reactions with shared epitopes between inner ear proteins and microbial proteins, the induction of damage associated with sustained high levels of cytokines and chemokines, or the presence of immunogenic factors producing a persistent inflammatory response in the inner ear.…”
Section: Genetic MDmentioning
confidence: 99%
“…Regarding MD, several hypotheses have been proposed to explain the appearance of autoimmune responses in the inner ear, including the appearance of cross-reactions with shared epitopes between inner ear proteins and microbial proteins, the induction of damage associated with sustained high levels of cytokines and chemokines, or the presence of immunogenic factors producing a persistent inflammatory response in the inner ear. 36 Studies in animals have experimentally induced an immune-mediated EH after antigen exposure. Moreover, studies in MD patients demonstrated the presence of antibodies against type II collagen, a component of connective tissue in the inner ear.…”
Section: Genetic MDmentioning
confidence: 99%
“…aging [24][25][26] , noise exposure 27 , the use of ototoxic drugs (28), autoimmune diseases [29,30] and other conditions [31][32][33][34][35] . According to WHO data, around 466 million people worldwide have disabling hearing loss, and 34 millions of these are children 36 .…”
Section: Benefits Of Hearing Dogsmentioning
confidence: 99%
“…[6] The prevalence of SNHL and the phenotypes are highly variable among the different diseases and between individuals with the same disease. SNHL has been reported in autoimmune diseases with a frequency as high as 80-90% and only in isolated cases in some diseases; however, the exact prevalence of ISNHL in these disorders is still unknown (reviewed by Ralli, et al [10] ). Immune responses localized to the inner ear cause diseases in which HL is the primary clinical manifestation, such as autoimmune inner ear disease, Meniere's disease, otosclerosis, cochlear vasculitis and sudden hearing loss.…”
Section: Isnhl In Autoimmune and Autoinflammatory Diseasesmentioning
confidence: 99%
“…[12,13] The pathophysiology of ISNHL is not clearly known, however, autoantibody (against inner ear antigens) driven cell-mediated cytotoxicity, complement activation and immune-complex deposition, have been proposed as possible mechanisms. [10] Chronic activation of selfreactive helper T-cells play a role in damaging the cochlear sensory hair cells and supporting cells. Deposition of immune-complexes in the labyrinthine artery has been proposed as a crucial factor in immune-mediated SNHL.…”
Section: Immune Responses and Mechanism Of Isnhlmentioning
confidence: 99%